Physical activity and physical fitness level among primary school children in Sekolah Kebangsaan Puncak Alam 2, Puncak Alam, Selangor / Aini Zainudin ... [et al.] - Zainudin, Aini; Mohd Yatim, Hanisah; Mohd Kamarul Zaman, Rosshaniszan; Wan Salehuddin, Wan Safirah Hakimah (2014)
Physical activity and physical fitness play important roles in determining the body weight status and health outcomes of an individual. This study aimed to determine the association between physical activity and physical fitness level with body mass index (BMI) and waist circumference and to determine the association between physical activity levels with physical fitness level among primary school children in Sekolah Kebangsaan Puncak Alam 2, Puncak Alam. Total of 321 school children were randomly selected in this study. Students' demographic, physical activity behaviors and physical fitness evaluation were collected. Anthropometric measurements were taken to assess students' nutritional status and BMI status. Physical activity behaviours were assessed using Physical Activity Questionnaire for Older Children (PAQ-C). Meanwhile, physical fitness assessed using four types of fitness test which are one-minute sit-up test, hand-grip test, sit-and-reach test, and Progressive Aerobic Cardiovascular Endurance Run Test (PACER) test. The results showed that school children are facing overweight which is 41 % while it is about 56% of children are obesity. This study found that, there is no significant between the physical activity score and the BMI status by using Pearson test. On the other hand, physical fitness shows there are no significant differences between groups BMI by using Independent T-test. There is also no significant different between sit and reach test (p=O. l 08), both hand grip test (left, p=0.85; right, p=0.112) between physical activity score using Independent T-test. It is recommended that physical activity that encourages health related fitness be intensified among school children in order to overcome these problems.